An Aggregate Production Planning Strategy Selection Methodology based on Linear Physical Programming - Gulsun, Bahadır; Tuzkaya, Gulfem; Tuzkaya, Umut R; Onut, Semih (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0in; margin-right:-1.45pt; margin-bottom:0in; margin-left:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-layout-grid-align:none; punctuation-wrap:simple; text-autospace:none; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:ZH-CN; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> In this paper, a multi-objective model for aggregate production planning is presented which includes two objectives: (1) minimized cost and (2) minimized effect on the workforce motivation level caused by hire/layoff decisions. Then, six strategies are considered and the most appropriate one is determined to structure the plan. These strategies are set the regular time production quantities in a certain value which is unique for each. A preference based optimization method called Linear Physical Programming (LPP) is used to solve the model. A forecasting phase which chooses the convenient method to forecast the demand for planning horizon is embedded to study in addition to application of LPP to an APP model as another key contribution of this paper. <!–EndFragment–>